Malnutrition among the older adult: an additional challenge for the rehabilitation team-insights of a small population of Switzerland - Miletic, Bojan; Sutter, Yves; Starčević-Klasan, Gordana; Courteney, Udo; Jelovica, Lejla; Lekić, Andrica; Šegulja, Silvije (Frontiers in Public Health, 2024)
Introduction Nutritional deficiency among the older adult is a widespread concern, significantly affecting their health. The prevalence of malnutrition increases with age, concurrent health conditions, and the level of care provided. Hospital stays can affect as 90% of the older adult. Malnutrition can hinder efforts to improve health and regain function in individuals undergoing rehabilitation. This study aims to assess the frequency of malnutrition among geriatric rehabilitation patients. Materials and methods A retrospective quantitative analysis was conducted on 357 patients admitted to the geriatric unit at Lucerne Cantonal Hospital Wolhusen in Switzerland. The patients’ nutritional status was evaluated using the standardized Mini Nutritional Assessment Long Form questionnaire. Results The initial analysis indicated a considerable prevalence of malnutrition among the geriatric population: 31.1% were identified as malnourished (MNA < 17), while an additional 35.8% were at risk of malnutrition (MNA 17–23.5), totaling 66.9% of patients. The Kruskal-Wallis ANOVA test revealed a statistically significant difference in MNA scores among different age groups (p = 0.035). Statistical analysis also suggested a slightly higher prevalence of malnutrition among female patients. The duration of rehabilitation varied from 20.07 ± 6.93 to 22.20 ± 7.50 days, with longer durations associated with lower MNA scores. A correlation analysis between MNA values and body mass index (BMI) showed a positive correlation coefficient (r = 0.56), indicating that lower MNA scores were associated with lower BMI and vice versa. Conclusion Malnutrition is prevalent among individuals over 65 years old, highlighting the importance of regular and timely nutritional assessments for geriatric patients to mitigate the complications and enhance prognoses in both acute care and rehabilitation settings. Such assessments can also improve the efficacy of rehabilitation programs and potentially reduce the duration of rehabilitation, thus carrying significant economic implications.